Sanctity in Buddhism - Spae, Joseph (Journal of Dharma, 1983)
To outsiders, Buddhism may initially appear to be filled with contradictions : doctrinally it seems to deny the existence of God and yet existentially it speaks of the human capacity to meet and imitate superhuman saints and saviours. While Buddhist teaching denies the existence of an immortal soul it nevertheless emphasizes personal continuity within a multitude of rebirths until liberation or enlightenment is attained. To Buddhists, however, these contradictions are only apparent and marginal.